Literary discourse pragmatics: literary communication - Lada Ferreras, Ulpiano (Tropelías: Review of Literary Theory and Comparative Literature, 1999)
The studies of literary pragmatics which consider it as one of the three levels of semiology together with syntax and semantics, have developed following the three aspects of the text: productive (authorial criticism) communicative (semiotics of the communication and the speech acts theory) and receptive (aesthelics of reception). In the present work we have started from the communicative orientation which has its base in the semiotics of communication. After going through the theory of the literary communication, from Bühler and Mukarovsky to the most recent critical contributions we maintain that a suitable method can be derived from this theory to undertake the study of literature from the pragmatics point of view,